MACHINE VISION AND GLOBAL POSITIONING SYSTEM FOR AUTONOMOUS ROBOTIC NAVIGATION IN AGRICULTURE: A REVIEW - Rahmadian, Reza; Widyartono, Mahendra (Universitas Negeri Surabaya, 2017)
Interest on robotic agriculture system has led to the development of agricultural robots that helps to improve the farming operation and increase the agriculture productivity. Much research has been conducted to increase the capability of the robot to assist agricultural operation, which leads to development of autonomous robot. This development provides a means of reducing agriculture?s dependency on operators, workers, also reducing the inaccuracy caused by human errors. There are two important development components for autonomous navigation. The first component is Machine vision for guiding through the crops and the second component is GPS technology to guide the robot through the agricultural fields.